A rare case of signet ring cell lymphoma: Diagnosis aided by immunofluorescent staining - Charusheela R Gore; N K Panicker; Harsh Kumar; Archana Buch; S S Chandanwale (Journal of Cytology, 2017)
Signet ring cell lymphomas are the proliferations of malignant lymphoid cells containing cytoplasmic vacuoles or globules which displace the nuclei, imparting it a signet ring appearance. This rare tumor is a variant of non-Hodgkin lymphoma. Signet ring appearance is due to cytoplasmic accumulation of immunoglobulin or vacuoles derived from multivesicular bodies. These cells, particularly with cytoplasmic vacuoles, may be mistaken for adenocarcinoma cells. We are presenting one such case where immunofluorescence helped us to demonstrate the immunoglobulins on fine needle aspiration smears. This is an innovative technique and has not been reported earlier. Our aim of presenting this case is to review the awareness of this rare lymphoma among pathologists to give due consideration for avoiding inappropriate investigations and treatment.